Peningkatan Hasil Belajar PKn melalui Pembelajaran Kooperatif Tipe Group Investigation pada Murid Kelas IV SD Inpres Boronguntia Kecamatan Bajeng Kabupaten Gowa (JED (Jurnal Etika Demokrasi), 2018)
This study aims to improve the learning outcomes of Citizenship Education through the implementation of the Group Investigation learning model in fourth grade students of Inpres Boronguntia Subdistrict Bajeng District of Gowa Regency. Subjects in this study were fourth graders Inpres Boronguntia District Bajeng District Gowa regency as many as 17 people consisting of 10 men and 7 women. This type of research is a classroom action research consisting of two cycles in which each cycle is held for four meetings. Each cycle consists of 4 stages: planning, action, observation and reflection. Data collection techniques used are observations and test results of learning are analyzed by quantitative and qualitative analysis techniques. The results showed that in the first fully completed cycle of 17 students only 5 students or 29.41% who fulfilled the Minimum Exhaustiveness Criteria (KKM) with an average score of 56.47 or in the medium category. While in the second complete cycle of 17 students is 13 students or 76.47% who meet the Minimum Exhaustiveness Criteria (KKM) with an average value obtained for 86.67 or are in very high category.Keywords: Learning Model, Group Investigation, Learning Outcomes, Citizenship Education